Biotransformação de diterpenos utilizando culturas de Fungos endofíticos e filamentosos - Siqueira, Caroline Duarte (2016)
Biotransformations are reactions of organic compounds carried out by isolated microorganisms, plants or enzymes. The transformation of a particular compound can be carried out in functional groups with or without degradation of its skeletons. Microorganisms are widely used in metabolism studies, since they catalyze chemo- , regio- and stereospecific reactions, which are often similar to those catalyzed by humans. In this context, this work had the objective of studying the microbial metabolism of three diterpenes with estemodane, trachylobano and latirano skeletons, using endophytic and filamentous fungi. Biotransformation experiments of aphidicolin with fungi Cunninghamella echinulata ATCC 8688ª, Chaetomium globosum ATCC 56726, Beauveria bassiana ATCC 7159 e o endofítico Penicilium crustosum VR4. Among the microorganisms used, only Chaetomium globosum ATCC 56726 gave a known 3-keto derivative and the major in vivo metabolising product. An incubation of the ent-7α-acetoxitraquiloban-18-oico, was used the fungus Mucor rouxii NRRL 1894, wich gaves C-17 hidroxiderivado. For the third substrate under study, (2S*,3S*,4R*, 5R*,9S*, 11R*, 15R*) -3,5,15-triacetoxi-14- oxolatira-6 (17), (12E)-dieno, two endophytic fungi strains were used: Botrytis cinerea UCA 996 e Mucor circinelloide NRRL 3631 (+). Only the fermentation with the species of Mucor gaves a C-8 hydroxylated derivative.